KAJIAN PERUBAHAN TINGGI MUKA LAUT PADA SAAT SIKLON TROPIS DAHLIA DI PESISIR LAMPUNG - Ariwibowo, Fajar Sidiq; Fadlan, Ahmad; Triatmoko, Danu (Pusdiklat BMKG, 2021)
This study aims to determine changes in the components of wind direction and speed during tropical cyclones by utilizing the ECMWF Era-Interim Reanalysis model data analyzed in the form of a time series graph. In addition, to determine the effect of the Dahlia Tropical Cyclone on changes in sea level on the Lampung Coast, a study was conducted by simulating sea level changes using the Delft-3d hydrodynamic model during the tropical cyclone event. The method used is comparative by comparing the output of hydrodynamic models to tidal measurements at 2 research points, namely Krui and Kota Agung tides. The data used are FNL wind data with a grid resolution of 0.25⁰ x 0.25⁰ and bathymetry data from gebco with a resolution of 30 seconds. The results showed that the performance of the hydrodynamic model was able to represent sea level well where the RMSE value was 0.36 for Krui Pasut Station, 0.23 for Kota Agung Pasut Station. While the correlation coefficient for Krui Pasut Station is 0.87 and 0.82 for Kota Agung tide station.